PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP RESPON INVESTOR PADA SEKTOR PROPERTI, REAL ESTATE, DAN KONSTRUKSI BANGUNGAN DI INDONESIA - Seraphine, Angelina (Business Accounting Review, 2015)
Nowadays, stakeholders should be maintained well by the companies in order to be sustained in business and reach the long term goal. The purpose of this research was to study the effect of corporate social responsibility (CSR) on the investor response on the listed companies on the property, real estate, and building construction sector in IDX between 2008 and 2012. The disclosure of CSR was proxied by the criterias on Global Reporting Initative (GRI) Index and investor response was proxied by cummulative abnormal return (CAR). In this research, return on asset (ROA), firm size (Fsize), debt to equity ratio (DER), and market share (Mshare) were used as control variables. The method used for data processing of 176 firm years was multiple regression analysis by using SPSS software 20th version. The result showed that CSR had positive significant effect on CAR.Â  ROA, Fsize, and Mshare as control variables had no effect on CAR, meanwhile, DER had positive significant effect on CAR.